Variation in mouse chemical signals is genetically controlled and environmentally modulated - Romana Stopková; Tereza Matějková; Alica Dodoková; Pavel Talacko; Petr Zacek; Radislav Sedlacek; Jaroslav Piálek; Pavel Stopka (Scientific Reports, 2023)
Abstract In most mammals and particularly in mice, chemical communication relies on the detection of ethologically relevant fitness-related cues from other individuals. In mice, urine is the primary source of these signals, so we employed proteomics and metabolomics to identify key components of chemical signalling. We show that there is a correspondence between urinary volatiles and proteins in the representation of genetic background, sex and environment in two house mouse subspecies Mus musculus musculus and M. m. domesticus. We found that environment has a strong influence upon proteomic and metabolomic variation and that volatile mixtures better represent males while females have surprisingly more sex-biased proteins. Using machine learning and combined-omics techniques, we identified mixtures of metabolites and proteins that are associated with biological features.